Studying the quality of life using the SF-36 questionnaire in patients with Rheumatoid arthritis - Gafforov, Xudoyor Xudoyberdiyevich (Science and Education, 2023)
Rheumatoid arthritis (RA) is a chronic progressive joint disease that leads to disability of patients. Of course, the disease affects the quality of life of patients with RA, but not enough attention is paid to the study of this issue by practitioners. Therefore, it is quite important to understand the factors leading to the deterioration of the physical and mental condition of this contingent of patients. Objective: To determine the factors affecting the quality of life of patients with rheumatoid arthritis based on data obtained from a questionnaire with using the sf-36 questionnaire. Tasks: 1. To conduct a questionnaire on the quality of life in patients with rheumatoid arthritis using the SF-36 questionnaire. 2. To conduct a comparative analysis of the results. 3. To identify factors affecting the quality of life of patients with rheumatoid arthritis. Material and methods. The study included 42 patients (average age 55±21.61 years) who were treated in the rheumatology department of the 1st clinic of SAMMU in 2020 - 2022. This group of patients was surveyed using the SF-36 quality of life questionnaire. Results and their discussion. Factors affecting the quality of life of a patient with RA have been identified: age more than 65 years,duration of the disease more than 10 years. Female gender (physical component only) Conclusions: 1. All the surveyed patients with rheumatoid arthritis had a decrease in the quality of life. 2. Risk factors for reducing the quality of life in patients with RA are age over 65 years, duration of the disease for more than 10 years and gender characteristics (belonging to the female sex - only by physical component) 3. Assessment of individual components of quality reduction in patients with RA will allow targeted preventive measures to increase the level of their physical and psycho-emotional state.